2003
DOI: 10.1074/jbc.m304417200
|View full text |Cite
|
Sign up to set email alerts
|

Closely Related G-protein-coupled Receptors Use Multiple and Distinct Domains on G-protein α-Subunits for Selective Coupling

Abstract: The molecular basis of selectivity in G-protein receptor coupling has been explored by comparing the abilities of G-protein heterotrimers containing chimeric G␣ subunits, comprised of various regions of G i1 ␣, G t ␣, and G q ␣, to stabilize the high affinity agonist binding state of serotonin, adenosine, and muscarinic receptors. The data indicate that multiple and distinct determinants of selectivity exist for individual receptors. While the A1 adenosine receptor does not distinguish between G i1 ␣ and G t ␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 27 publications
4
38
0
2
Order By: Relevance
“…D2N, in common with several other receptor loop peptides, exhibits modest GEF activity on G␣ subunits in vitro with a selectivity profile analogous to the cognate full-length receptor (Nanoff et al, 2006). We found that D2N binds to the ␣4/␤6 loop region of G␣, previously identified as a critical receptor contact site important for G␣-coupling selectivity (Hamm et al, 1988;Onrust et al, 1997;Slessareva et al, 2003; (Figs. 4 and 6).…”
Section: Structural Determinants Of G-protein Activation By Gpcrs 225mentioning
confidence: 87%
“…D2N, in common with several other receptor loop peptides, exhibits modest GEF activity on G␣ subunits in vitro with a selectivity profile analogous to the cognate full-length receptor (Nanoff et al, 2006). We found that D2N binds to the ␣4/␤6 loop region of G␣, previously identified as a critical receptor contact site important for G␣-coupling selectivity (Hamm et al, 1988;Onrust et al, 1997;Slessareva et al, 2003; (Figs. 4 and 6).…”
Section: Structural Determinants Of G-protein Activation By Gpcrs 225mentioning
confidence: 87%
“…Notably, the ␣4 helix residues Q304 and E308 contacted directly by D2N basic residues (Fig. 2B) have been implicated in the G protein coupling specificity of the 5-HT 1A serotonin receptor (21). Mutation of these two ␣4 helix residues within G␣ i1 to the corresponding residues in G␣ s (Q304R/ E208L; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…D2N engages a triad of residues on the ␣4 helix and ␤6 strand (Q304/E308 and T321, respectively; Fig. 2B) that were implicated in studies using G␣ chimera (19)(20)(21) in the coupling specificity and GEF activity of the 5-HT 1A serotonin receptor. Binding of D2N results in displacement of the G␣ i1 ␤6 strand with respect to the unbound state ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Além de Wess et aI. (240), Graber et alo (242,243) também mostraram através de mutações que os últimos cinco resíduos do C-terminal de Ga são importantes para o acoplamento da proteína G com o receptor muscarínico. Essa região forma uma dobra (3, conforme discutido acima (seção 5.2.1).…”
Section: Interação Do Cg Com Fragmentos Do Receptor a Tia De Angiotenunclassified
“…Pin et aI. (243,244) também mostraram que a posição -3 e --4 (-1 corresponde ao último resíduo) em G u é importante para o acoplamento com o receptor de glutamato.…”
Section: Interação Do Cg Com Fragmentos Do Receptor a Tia De Angiotenunclassified